A preparation method of double cross-linked self-reinforced thermal conductive EPDM rubber

By introducing dual cross -linking dynamic covalent units and preparing hybrid heat conduction fillers, the problem of insufficient thermal thermal conductivity of Sanyuan E -C rubber has been solved, and the combination of high heat conductive and high -powered properties is achieved, which is suitable for electronic device thermal management.

CN118812968BActive Publication Date: 2025-01-28TAIZHOU QIHE NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410421571.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2025-01-28
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the thermal conductivity of EPDM rubber while maintaining high elasticity and mechanical properties. A large amount of filling thermally conductive fillers will destroy the processability of the rubber.

Method used

The dual cross -linking dynamic covalent unit is introduced through chemical reactions, and the use of fluorinated graphene, boron nanomide tablets and liquid metals are used to prepare hybrid heating fillers, combined with thermal suppression preparation methods to form dual cross -linking self -enhanced thermal conductivity ethm rubber.

Benefits of technology

It significantly improves the thermal conductivity and mechanical performance of the Sanyuan Ethiopian Rubber. At the same time, the interface thermal resistance is reduced, the high -temperature service performance is maintained, and it is suitable for electronic device thermal management fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812968B_ABST
    Figure CN118812968B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a double-crosslinked self-reinforced thermal conductive EPDM rubber, which is characterized in that firstly, an imine bond and a disulfide bond are simultaneously introduced into the same crosslinking section of liquid EPDM (LEPDM) through a chemical reaction to construct a double-crosslinked dynamic covalent unit. During the processing, the sulfur free radicals generated by the breakage of the dynamic covalent disulfide bond can attack the double bonds of the LEPDM side chains and / or couple with the allyl sites to enhance the mechanical properties and realize the self-reinforcement characteristics; the liquid metal (LM) is encapsulated by using fluorinated graphene (FG) through ultrasonic dispersion. The LM is self-assembled between FG layers, and a boron nitride nanosheet (BNNS) matching the FG phonon is used as a binder to prepare a BNNS / FG@LM hybrid thermal conductive filler, which exerts a synergistic thermal conductive effect, is dispersed in a LEPDM rubber matrix by mixing, and a terpolymer EPDM rubber composite material with double cross-linked self-enhanced thermal conductivity is prepared by hot pressing. The cross-linked LEPDM molecular chain sulfur radicals form a metal-sulfur coordination bond with FG@LM, which reduces the interfacial thermal resistance, increases the density of the thermal conductive network, and effectively improves the thermal conductivity of the terpolymer EPDM rubber. The double cross-linked self-enhanced thermal conductive terpolymer EPDM prepared by the present invention has a simple preparation method, does not require the addition of a vulcanizing agent, has excellent mechanical properties and thermal conductivity, and can be used in the field of heat dissipation of electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing double-crosslinked self-reinforced thermal conductive ethylene propylene diene monomer rubber, and belongs to the field of rubber material preparation. Background Art

[0002] The advent of the post-Moore era has led to the development of electronic devices towards miniaturization, high integration and high power density. The heat dissipation of electronic devices has become the key to their stable and reliable operation. If the heat accumulated during operation cannot be dissipated in time, it will seriously affect the working efficiency of electronic devices and shorten their service life. Therefore, thermal conductive materials must be used to connect electronic components and external systems to establish an effective heat transfer channel to achieve the purpose of rapid heat dissipation and extend service life.

[0003] Rubber-based elastomers have unique high flexibility and elasticity and can be used as candidate materials for thermal management. However, their amorphous aggregate structure results in low intrinsic thermal conductivity (~ 0.2 W / mK), which mainly relies on phonon heat conduction. At present, the preparation of thermally conductive rubber mainly adopts the method of blending and compounding, that is, a large amount of high thermal conductivity nanofillers are filled into the rubber matrix to achieve thermal conductivity. However, due to the interface compatibility, dispersibility and interface thermal resistance, there is a large gap between the experimental value and the theoretical value of thermal conductivity enhancement, which cannot meet the use requirements. In addition, large amounts of filling will also destroy the elasticity, mechanical properties and processability of the rubber, increase the rigidity, and limit its application. Therefore, how to prepare rubber composite materials with high elasticity and thermal conductivity is of great significance to the field of thermal management of electronic equipment.

[0004] EPDM rubber has excellent aging resistance, heat resistance and elasticity, making it an ideal matrix for thermally conductive rubber, but unmodified EPDM rubber has poor thermal conductivity and cannot meet the application performance requirements in the field of heat dissipation of electronic equipment. Chinese patents CN201611072729.5 and CN201810894227.3 disclose a super thermally conductive EPDM rubber and a graphene-modified EPDM rubber composite material and a preparation method thereof, respectively preparing a thermally conductive EPDM rubber composite material by adding zinc oxide and using nano inorganic thermal conductive fillers such as nano oxides, carbides, nitrides and modified graphene as fillers, but the added filler content is high and no specific thermal conductivity is given. Yu Pinxuan et al., Insulation Materials, 2021, 54(6):26-31, by filling EPDM with multi-scale alumina, nano zinc oxide single filler and the composite of the two, when the filling amount of both is 200 parts, the thermal conductivity of the composite material reaches 1.16 W / mK; Zhao Xifeng et al., Plastic Science and Technology, 2020, 48(04):59-62, using nano alumina as filler, when its content increases to 100 parts, the thermal conductivity of the composite material increases to 0.53 W / mK, but the amount of thermal conductive filler added is as high as hundreds of parts, and the increase in thermal conductivity efficiency is limited. He et al., Polymer Composites, 2017, 38(5):870-876, systematically studied the change of thermal conductivity of EPDM / expanded graphite composites with filler content. When the content of expanded graphite was 25.8 vol%, the thermal conductivity of the composite material reached 0.910 W / mK, which is 4.5 times that of unfilled EPDM, but the improvement of thermal conductivity is still very limited. At present, the preparation of thermal conductive EPDM rubber still adopts the traditional method of blending and filling a large amount of thermal conductive fillers. There is still a lack of research on improving the thermal conductivity of EPDM rubber, and there is even less research on using a double cross-linked network to enhance the interface between the thermal conductive filler and the rubber matrix and reduce the interface thermal resistance.

[0005] Fluorinated graphene (FG) and boron nitride nanosheets (BNNS) are two-dimensional lamellar structures with high thermal conductivity and insulation. They can be used as ideal thermal conductive fillers for thermally conductive rubber elastomers. At the same time, their lamellar structures are conducive to improving the thermal stability and high-temperature service performance of rubber. Liquid metal (LM) has low interfacial thermal resistance and good mechanical deformation ability. It matches the elasticity and can be used as a buffer layer between the thermal conductive filler and the rubber matrix to effectively transfer stress. The preparation of BNNS / FG@LM hybrid thermal conductive filler can synergistically enhance thermal conductivity. At the same time, there is a hydrogen bond between the hybrid thermal conductive fillers, which is expected to reduce the interfacial thermal resistance. In addition, the preparation of double-crosslinked self-reinforced EPDM rubber, the use of free radicals generated by the breakage of dynamic crosslinking bonds and the coordination enhancement interaction of the hybrid thermal conductive filler to reduce the interfacial thermal resistance has not been reported. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation method of double cross-linked self-reinforced thermal conductive EPDM rubber in view of the deficiencies of the prior art. The method is characterized in that firstly, an imine bond and a disulfide bond are simultaneously introduced into the same cross-linking segment of liquid EPDM (LEPDM) through a chemical reaction to construct a double cross-linked dynamic covalent unit. During the processing, the sulfur free radicals generated by the breakage of the dynamic covalent disulfide bond can attack the double bonds of the LEPDM side chains and / or couple with the allyl sites to enhance the mechanical properties. No vulcanizing agent is required to achieve self-reinforcement characteristics. Graphene fluoride (FG) is used for the preparation of double cross-linked self-reinforced thermal conductive EPDM rubber by ultrasonic dispersion. For liquid metal (LM) encapsulation and LM self-assembly between FG layers, boron nitride nanosheets (BNNS) matching the FG phonons were used as binders to prepare BNNS / FG@LM hybrid thermal conductive fillers to exert synergistic thermal conductivity. They were dispersed in the LEPDM rubber matrix by mixing and hot-pressed to prepare EPDM rubber composites with double cross-linked self-enhanced thermal conductivity. The cross-linked LEPDM molecular chain sulfur radicals formed metal-sulfur coordination bonds with FG@LM, which reduced the interfacial thermal resistance, increased the density of the thermal conductive network, and effectively improved the thermal conductivity of EPDM rubber.

[0007] The object of the present invention is achieved by the following technical scheme, wherein the raw material fractions are all mass fractions unless otherwise specified.

[0008] A method for preparing double-crosslinked self-reinforced thermal conductive EPDM rubber, characterized in that the main raw material of the rubber is composed of the following components, calculated by mass fraction:

[0009] Liquid EPDM (LEPDM) 100 parts

[0010] Liquid metal (LM) 0.5-4 parts

[0011] Fluorinated graphene (FG) 3-10 parts

[0012] Boron nitride nanosheets (BNNS) 5-15 parts

[0013] 1-10 parts of compounds containing thiol and aldehyde groups

[0014] 5-12 parts of compounds containing amino groups and sulfur bonds

[0015] Wherein, the molecular weight of the liquid ethylene propylene diene monomer rubber (LEPDM) is 2000-8000;

[0016] The liquid metal (LM) is a gallium-indium alloy Ga75-In25;

[0017] The compound containing thiol and aldehyde groups is any one of 2-mercaptoacetaldehyde, 4-mercaptobenzaldehyde, and 3-mercapto-2-methyl-pentanal;

[0018] The compound containing an amino group and a sulfur bond is any one of 4,4'-diaminodiphenyl disulfide, diphenylcyclooctyne-disulfide-amino, 2,2'-diaminodiphenyl disulfide, and cystamine dihydrochloride;

[0019] The preparation method of the double-crosslinked self-reinforced thermal conductive EPDM rubber comprises the following steps:

[0020] 100 parts of LEPDM with a molecular weight of 2000-8000 are dissolved in cyclohexane to a concentration of 4-15wt%. 1-10 parts of compounds containing thiol and aldehyde groups are added to the above solution, stirred evenly, and reacted continuously with stirring at 50-80°C for 2-4 hours to graft the aldehyde group onto the rubber molecular chain. Then 5-12 parts of compounds containing amino groups and sulfur bonds are added as reaction monomers, and the reaction is continued at 60-85°C for 2-8 hours. Through the reaction of aldehyde groups and amino groups, imine bonds and disulfide bonds are simultaneously introduced into the same cross-linked network, flocculated, and vacuum dried at 50°C for 6 hours to obtain double-crosslinked self-reinforced LEPDM.

[0021] 3-10 parts of fluorinated graphene (FG) powder were ultrasonically dispersed in 300-1000 parts of deionized water to form a uniform dispersion, 0.5-4 parts of liquid metal (LM) were added and ultrasonicated for 15 min to promote the interaction between LM and FG and the self-assembly of LM on the FG sheet, and then 5-15 parts of boron nitride nanosheets (BNNS) were added and ultrasonically dispersed for 1-3 h to promote the π-π interaction between BNNS and FG. After the reaction was completed, the mixture was filtered and dried in vacuum at 40 °C to obtain BNNS / FG@LM hybrid thermal conductive filler.

[0022] The prepared BNNS / FG@LM was added into the double-crosslinked LEPDM system, mixed evenly on an open mill at room temperature, and hot pressed at 100-150°C and 8-12 MPa for 2-18 min to obtain a double-crosslinked self-reinforced thermal conductive EPDM rubber.

[0023] The present invention has the following advantages: a dynamic imine bond and a disulfide bond are simultaneously introduced into the same cross-linking segment of liquid ethylene propylene diene monomer (LEPDM) by chemical reaction to construct a double-cross-linked dynamic covalent unit, that is, two covalent bonds are simultaneously present on the cross-linking bond, thereby realizing covalent cross-linking of LEPDM, and also modifying LEPDM with organic functional groups to introduce reaction sites; phonon-matched fluorinated graphene (FG) and boron nitride nanosheets (BNNS) are used as thermal conductive fillers, and liquid metal (LM) is used as the third component, and the encapsulation of FG to LM and the bonding of LM to the FG sheet are realized by ultrasonic dispersion. The hybrid thermal conductive filler BNNS / FG@LM was prepared by self-assembly; the hybrid thermal conductive filler was dispersed in the LEPDM rubber matrix by mixing, and the EPDM rubber composite material with double cross-linked self-enhanced thermal conductivity was prepared by hot pressing. The sulfur free radicals generated by the dynamic covalent disulfide bond rupture during the processing can attack the double bonds of the LEPDM side chain and / or couple with the allylic site to enhance the mechanical properties and achieve self-enhancement characteristics. At the same time, the sulfur free radicals of the LEPDM molecular chain and FG@LM form metal-sulfur coordination bonds, reduce the interfacial thermal resistance, increase the density of the thermal conductive network, and effectively improve the thermal conductivity of the EPDM rubber. At the same time, the BNNS / FG@LM layer structure is conducive to improving the thermal stability and high-temperature service performance of the rubber, and is conducive to maintaining high thermal conductivity under high-temperature working environment. The preparation method is simple, and the mechanical properties are enhanced without adding other fillers and vulcanization systems. At the same time, the thermal conductivity is significantly improved, which has certain advantages in the field of thermal management of electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the reaction process and mechanism of double-crosslinked self-reinforced EPDM rubber.

[0025] Figure 2 Schematic diagram of the assembly of BNNS / FG@LM hybrid thermal conductive filler. DETAILED DESCRIPTION

[0026] The present invention is further described below through specific examples. It should be noted that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make non-essential improvements and adjustments to the present invention based on the contents of the present invention described above. Example

[0027] 100 parts of LEPDM with a molecular weight of 2000 were dissolved in cyclohexane with a concentration of 12wt%. 2 parts of 2-mercaptoacetaldehyde were added to the above solution and stirred evenly. The mixture was stirred and reacted continuously at 60°C for 2 h to graft the aldehyde group onto the rubber molecular chain. Then 6 parts of 4,4'-diaminodiphenyl disulfide were added as reaction monomers and the reaction was continued at 70°C for 4 h. The imine bond and disulfide bond were introduced into the same cross-linked network through the reaction of the aldehyde group and the amino group. The mixture was flocculated and dried in vacuum at 50°C for 6 h to obtain double-cross-linked self-reinforced LEPDM.

[0028] 3 parts of fluorinated graphene (FG) powder were ultrasonically dispersed in 300 parts of deionized water to form a uniform dispersion. 0.8 parts of liquid metal (LM) was added and ultrasonication was continued for 15 min to promote the interaction between LM and FG and the self-assembly of LM on the FG sheet. Then 5 parts of boron nitride nanosheets (BNNS) were added and ultrasonic dispersion was continued for 1 h to promote the π-π interaction between BNNS and FG. After the reaction was completed, the mixture was filtered and dried in vacuum at 40 °C to obtain BNNS / FG@LM hybrid thermal conductive filler.

[0029] The prepared BNNS / FG@LM was added to the double-crosslinked LEPDM system, mixed evenly at room temperature on an open mill, and hot pressed at 110°C and 8 MPa for 5 min to obtain a double-crosslinked self-reinforced thermal conductive EPDM rubber. The tensile strength of the EPDM composite rubber was 2.47 MPa, the elongation at break was 624%, the thermal conductivity was 1.471 W / mK, and the thermal conductivity was 1.233 W / mK under the working conditions of 70°C´12 h. Example

[0030] 100 parts of LEPDM with a molecular weight of 4000 were dissolved in cyclohexane with a concentration of 10wt%. 4 parts of 4-mercaptobenzaldehyde were added to the above solution and stirred evenly. The mixture was stirred and reacted continuously at 70°C for 3 h to graft the aldehyde group onto the rubber molecular chain. Then 8 parts of 2,2'-diaminodiphenyl disulfide were added as reaction monomers and the reaction was continued at 75°C for 6 h. The imine bond and disulfide bond were introduced into the same cross-linked network through the reaction of the aldehyde group and the amino group. The mixture was flocculated and dried in vacuum at 50°C for 6 h to obtain double-cross-linked self-reinforced LEPDM.

[0031] 5 parts of fluorinated graphene (FG) powder were ultrasonically dispersed in 500 parts of deionized water to form a uniform dispersion. 2 parts of liquid metal (LM) were added and ultrasonicated for 15 min to promote the interaction between LM and FG and the self-assembly of LM on the FG sheet. Then 8 parts of boron nitride nanosheets (BNNS) were added and ultrasonically dispersed for 2 h to promote the π-π interaction between BNNS and FG. After the reaction, the mixture was filtered and dried in vacuum at 40 °C to obtain BNNS / FG@LM hybrid thermal conductive filler.

[0032] The prepared BNNS / FG@LM was added to the double-crosslinked LEPDM system, mixed evenly at room temperature on an open mill, and hot pressed at 130°C and 10 MPa for 8 min to obtain a double-crosslinked self-reinforced thermal conductive EPDM rubber. The tensile strength of the EPDM composite rubber was 3.52 MPa, the elongation at break was 774%, the thermal conductivity was 2.161 W / mK, and the thermal conductivity was 1.638 W / mK under the working conditions of 70°C´12 h. Example

[0033] 100 parts of LEPDM with a molecular weight of 6000 were dissolved in cyclohexane with a concentration of 8wt%. 6 parts of 3-mercapto-2-methyl-pentanal were added to the above solution and stirred evenly. The mixture was stirred and reacted continuously at 70°C for 4 h to graft the aldehyde group onto the rubber molecular chain. Then 8 parts of cystamine dihydrochloride were added as a reaction monomer and the reaction was continued at 80°C for 6 h. The imine bond and disulfide bond were introduced into the same cross-linked network through the reaction of the aldehyde group and the amino group. The mixture was flocculated and dried in vacuum at 50°C for 6 h to obtain double-cross-linked self-reinforced LEPDM.

[0034] 8 parts of fluorinated graphene (FG) powder were ultrasonically dispersed in 800 parts of deionized water to form a uniform dispersion. 3 parts of liquid metal (LM) were added and ultrasonicated for 15 min to promote the interaction between LM and FG and the self-assembly of LM on the FG sheet. Then 10 parts of boron nitride nanosheets (BNNS) were added and ultrasonically dispersed for 3 h to promote the π-π interaction between BNNS and FG. After the reaction, the mixture was filtered and dried in vacuum at 40 °C to obtain BNNS / FG@LM hybrid thermal conductive filler.

[0035] The prepared BNNS / FG@LM was added to the double-crosslinked LEPDM system, mixed evenly at room temperature on an open mill, and hot pressed at 140°C and 10 MPa for 10 min to obtain a double-crosslinked self-reinforced thermal conductive EPDM rubber. The tensile strength of the EPDM composite rubber is 4.64 MPa, the elongation at break is 759%, and the thermal conductivity is 2.905 W / mK. Under the working conditions of 70°C´12 h, its thermal conductivity is 2.243 W / mK. Example

[0036] 100 parts of LEPDM with a molecular weight of 8000 were dissolved in cyclohexane with a concentration of 4wt%. 10 parts of 4-mercaptobenzaldehyde were added to the above solution and stirred evenly. The mixture was stirred and reacted continuously at 65°C for 4 h to graft the aldehyde group onto the rubber molecular chain. Then 12 parts of diphenylcyclooctyne-disulfide bond-amino group were added as reaction monomers and the reaction was continued at 85°C for 8 h. The imine bond and disulfide bond were simultaneously introduced into the same cross-linked network through the reaction of the aldehyde group and the amino group. The mixture was flocculated and dried in vacuum at 50°C for 6 h to obtain double-cross-linked self-reinforced LEPDM.

[0037] 10 parts of fluorinated graphene (FG) powder were ultrasonically dispersed in 1000 parts of deionized water to form a uniform dispersion. 4 parts of liquid metal (LM) were added and ultrasonicated for 15 min to promote the interaction between LM and FG and the self-assembly of LM on the FG sheet. Then 15 parts of boron nitride nanosheets (BNNS) were added and ultrasonically dispersed for 3 h to promote the π-π interaction between BNNS and FG. After the reaction, the mixture was filtered and dried in vacuum at 40 °C to obtain BNNS / FG@LM hybrid thermal conductive filler.

[0038] The prepared BNNS / FG@LM was added to the double cross-linked LEPDM system, mixed evenly at room temperature on an open mill, and hot pressed at 150°C and 12 MPa for 15 min to obtain a double cross-linked self-reinforced thermal conductive EPDM rubber. The tensile strength of the EPDM composite rubber is 5.08 MPa, the elongation at break is 713%, the thermal conductivity is 3.142 W / mK, and the thermal conductivity is 2.532 W / mK under the working conditions of 70°C´12 h.

[0039] In summary, the double-crosslinked self-reinforced thermally conductive EPDM rubber prepared in the embodiment of the present invention has high mechanical properties and thermal conductivity, and still maintains high thermal conductivity after high-temperature service, and can be used in the field of thermal management of electronic devices.

Claims

1. A method for preparing a double-crosslinked self-reinforced thermal conductive EPDM rubber, characterized in that The main raw materials of the rubber are composed of the following components, calculated by weight: Liquid EPDM LEPDM 100 parts Liquid Metal LM 0.5-4 parts Fluorinated graphene FG 3-10 parts Boron nitride nanosheets BNNS 5-15 parts 1-10 parts of compounds containing thiol and aldehyde groups 5-12 parts of compounds containing amino groups and sulfur bonds Wherein, the molecular weight of the liquid ethylene propylene diene monomer rubber LEPDM is 2000-8000; The liquid metal LM is a gallium-indium alloy Ga75-In25; The compound containing thiol and aldehyde groups is any one of 2-mercaptoacetaldehyde, 4-mercaptobenzaldehyde, and 3-mercapto-2-methyl-pentanal; The compound containing an amino group and a sulfur bond is any one of 4,4'-diaminodiphenyl disulfide, diphenylcyclooctyne-disulfide-amino, 2,2'-diaminodiphenyl disulfide, and cystamine dihydrochloride; The preparation method of the double-crosslinked self-reinforced thermal conductive EPDM rubber comprises the following steps: Dissolve 100 parts of LEPDM with a molecular weight of 2000-8000 in cyclohexane to prepare a solution with a concentration of 4-15wt%, add 1-10 parts of a compound containing a thiol group and an aldehyde group to the above solution, stir evenly, and react continuously at 50-80°C for 2-4 hours to graft the aldehyde group on the rubber molecular chain, then add 5-12 parts of a compound containing an amino group and a sulfur bond as a reaction monomer, continue to react at 60-85°C for 2-8 hours, and simultaneously introduce an imine bond and a disulfide bond into the same cross-linked network through the reaction of the aldehyde group and the amino group, flocculate, and vacuum dry at 50°C for 6 hours to obtain a double-crosslinked self-reinforced LEPDM; 3-10 parts of fluorinated graphene FG powder are ultrasonically dispersed in 300-1000 parts of deionized water to form a uniform dispersion, 0.5-4 parts of liquid metal LM are added and ultrasonicated for 15 min to promote the interaction between liquid metal LM and fluorinated graphene FG and the self-assembly of liquid metal LM on the fluorinated graphene FG sheet, and then 5-15 parts of boron nitride nanosheets BNNS are added and ultrasonically dispersed for 1-3 h to promote the π-π interaction between BNNS and FG. After the reaction is completed, the mixture is filtered and vacuum dried at 40°C to obtain BNNS / FG@LM hybrid thermal conductive filler; The prepared BNNS / FG@LM was added into the double-crosslinked LEPDM system, mixed evenly on an open mill at room temperature, and hot pressed at 100-150°C and 8-12 MPa for 2-18 min to obtain a double-crosslinked self-reinforced thermal conductive EPDM rubber.

Citation Information

Patent Citations

  • Superconductor thermal ethylene propylene diene methylene rubber

    CN106700281A

  • Graphene-modified ethylene-propylene-diene monomer rubber composite material and preparation method thereof

    CN108976618A

  • Preparation method of bi-crosslinking network enhanced and stabilized ethylene propylene diene monomer rubber

    CN116426074A

  • Heat-conducting rubber composite material as well as preparation method and application thereof

    CN116478480A